Hyperreality of the postmodern narrative in the novel Andrukhovich’s «Perversion» (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article deals with and interprets the narrative aspects of some episodes of the novel «Perversion» by Yu. Andrukhovich, illustrating the phenomenon of  a hyperreality.The hyperreality is a prominent feature of postmodern creativity. By this concept, it is an idea of the world in which objective reality itself is relative, because the subject is not able to capture the whole reality or to offer it’s ideal variant, and generally they do not know what is reality and where it is. Hyperreality in the text is manifested in the effect of «virtual», simulated reality. This phenomenon is vividly represented in selected fragments depicting the same event: the opera Orpheus in Venice. It traces the blurring of the boundaries between the real and the imaginary and the creation of conditional worlds that are intertwined.According to Bordiard's «Theory of Signs», the events surrounding the opera «Orpheus in Venice» are described on the third and fourth levels of the signs. The presence of the publisher and his preface at the beginning of the novel, the intrinsically focussed story of Stakh Perfetsky masks that there is no corresponding reality behind the events described in the seminar (third-order simulacrum). A pictured action on the stage (fourth order of the simulacrum) also contributes to this. On the background of the chaotic staging of the opera, a seminar in Venice is perceived, as not a credible event at least as possible.The hyperreality is also traced in the episodes that illustrate the simulation of relationships between the characters of the novel: the unreality of real-world relationships where communication between people does not occur because, according to the words, there is no real depth of feelings. The heroine's behavior resonates with her attention to the hero's story. He sincerely talks about the tragedy he has experienced, but there is no confirmation to the truth of this story, because it is a story.The effect of the hyperreality in the postmodern text is achieved by the fact that the narrative strategy of the author causes a blurring of the boundary between fantasy and reality, true and simulated.
Keywords: postmodernism; hyperreality; simulacrum; narrative; narrator; focalization; discourse; narrative distance